PERAN NELAYAN PEREMPUAN DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA DI SINDANGLAUT, KAWASAN WISATA PANTAI CARITA, PANDEGLANG - Amalya, Neneng Tita; Sulistyani, Tri; Harsono, Yhonanda (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2023)
The purpose of this community service activity (PKM) is to spread enthusiasm in running a business that although at a small level, the benefits for family welfare can be felt in particular and the role of fisherwomen who support family welfare in general. The method used is by sharing knowledge and experience with the theme